Costochondral Grafting for Nasal Airway Reconstruction in an Infant With Frontonasal Dysplasia. Issue 1 (January 2019) - Fujisawa, Kou; Watanabe, Shoji; Kato, Motoi; Utsunomiya, Hiroki; Watanabe, Azusa
Abstract : Abstract: Frontonasal dysplasia (FND) is a congenital malformation of the central portion of the face, including the eyes, nose, and forehead. Owing to its rarity and wide spectrum of phenotypes, the optimal timing and technique of surgery remain controversial. Here, we report a case of a patient with FND, who presented with respiratory distress. The deformed nostrils were so small that the patient could not normally breathe through the nose immediately after birth. Rhinoplasty using a costochondral graft was performed at 16 months of age. After surgery, the nostrils enlarged and the appearance of the nose improved. Although congenital nasal deformity is frequently corrected during adolescence, surgery at an early stage can be considered when important issues are noted, such as inability to breathe through the nose.